Integrated Multi-Sectoral Approach for Planning of Carbon Capture and Storage Projects - Tianyuan Zhou; Guopeng Zhang; Zhiwei Li; Kathleen B. Aviso; Raymond R. Tan; Xiaoping Jia; Fang Wang (Chemical Engineering Transactions)
The chemical, mining, iron and steel, and power sectors are the main CO2 emitting industries in China. Promoting the low-carbon and green development of various sectors has become an important link to achieve dual carbon goals. Carbon capture and storage technologies are the important means of carbon sequestration. To optimally match the sources and sinks, an integrated approach which combines process integration with orthogonal experimental design method is developed. Through setting up the reservoirs of four sectors, carbon storage composite curves (CSCC) are developed to investigate CO2 sequestration from 2020 to 2060 to solve the problem of matching carbon sources and sinks. Then, the orthogonal experimental design is used to investigate the influence of the four factors (e.g., the start-up time, the number of the storages, the storage capacity, and the storage operation interval) on the CO2 storage. The optimal storage scheme is obtained. The matching of carbon sources and sinks at the regional scale will contribute to deploying CCS to realize carbon neutrality by 2060.